Peran pembelajaran Bahasa Indonesia bagi generasi milenial di era society 5.0 - Aryani, Laila Rahma (Maliki Interdisciplinary Journal, 2024)
Indonesian language learning has an important role and is an asset for the millennial generation in the era of society 5.0. Learning Indonesian is an alternative for the millennial generation in developing human resources so that they are able to balance advances in technology, education, the economy and solving social problems in the era of society 5.0. The development and improvement of human resources must of course be carried out by the millennial generation, which is characterized by having a creative personal character, always looking for and trying new things and cannot let go of its activities from existing information and communication technology. This condition makes Indonesian language learning must adapt to technological developments in the era of society 5.0. The millennial generation who believes more in User Generated Content (UGC) than one-way information makes this generation ten not to care about moral and ethical values in communicating and disseminating information in digital techhnology (social media). For this reason, with the existence of learning Indonesian for the millennial generation, it is hoped that they will be able to understand society 5.0, face the challenges and problems within it, and produce quality, intelligent and intellectual millennial generations.